Factor Analysis of Population Growth using Data Analytics - Girish, Anupama; Dey, Aditya; Sharma, Ankit; Jain, Ketan; Sanket, Kumar; Amutha, S; Babu, Ramesh D.R (International Journal of Computer Sciences and Engineering, 2018)
According to the estimation billionth person was born in 1804 and the second billionth was born about 123 years later in 1927. Since then it has taken humans 60 years to reach the 5 billion mark and now we are closer to population of 8 billion. India contributes about 20% of this population making it as the second most populous country in the world. Originally, most of the important predictions were made using the Malthusian growth models. The science of data analytics has opened up new possibilities in the creation of prediction graphs. Prediction graphs give useful information about tackling the problem of increasing population. R programming language is used to identify factors that impact the rate of change of population. Important factors such as literacy rate, death rate, religion and so on, deeply impact the rate of population growth. From the Kaiser-Meyer-Olkin test and Factor Analysis found that out of all factors that were considered, religious differences and migration rate were the most important factors affecting the rate of population growth.